2017
DOI: 10.1007/s10753-017-0587-4
|View full text |Cite
|
Sign up to set email alerts
|

A Chemically Modified Curcumin (CMC 2.24) Inhibits Nuclear Factor κB Activation and Inflammatory Bone Loss in Murine Models of LPS-Induced Experimental Periodontitis and Diabetes-Associated Natural Periodontitis

Abstract: The purpose of this study was to assess the effect of a novel chemically modified curcumin (CMC 2.24) on NF-κB and MAPK signaling and inflammatory cytokine production in two experimental models of periodontal disease in rats. Experimental model I: Periodontitis was induced by repeated injections of LPS into the gingiva (3×/week, 3 weeks); control rats received vehicle injections. CMC 2.24, or the vehicle, was administered by daily oral gavage for 4 weeks. Experimental model II: Diabetes was induced in adult ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
102
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(106 citation statements)
references
References 98 publications
(120 reference statements)
3
102
0
1
Order By: Relevance
“…Diabetes mellitus and periodontitis are complex chronic diseases with an established higher risk for the development periodontitis and future tooth loss in the presence of DM . CURC is a natural compound with promising effects in modulating the osteo‐immune‐inflammatory and antioxidant host response both in periodontally diseased sites and in diabetes and related complications . For the first time, this investigation assessed the natural curcumin's impact on the progression of EP in rats induced to DM.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Diabetes mellitus and periodontitis are complex chronic diseases with an established higher risk for the development periodontitis and future tooth loss in the presence of DM . CURC is a natural compound with promising effects in modulating the osteo‐immune‐inflammatory and antioxidant host response both in periodontally diseased sites and in diabetes and related complications . For the first time, this investigation assessed the natural curcumin's impact on the progression of EP in rats induced to DM.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of the morphometric evaluations of the current study revealed that DM induction promoted higher periodontal disease progression and that diabetic rats treated with daily CURC + INS, as well as those Non‐DM, presented lower linear bone loss values in periodontitis sites, suggesting that the combined use of CURC and INS, and not the substances used alone, may positively influence periodontal breakdown, even in the presence of DM. Although promising effects of natural CURC on periodontal tissues have already been revealed in earlier experimental and also clinical studies, only few information is available concerning the influence of a chemically modified CURC on periodontitis in the presence of a recognized at‐risk condition as diabetes mellitus and there are no data revealing the impact of a natural CURC in the progression of EP associated with DM. Of importance, although some evidence has suggested that certain chemically modified CURC shows improved solubility and bioavailability in comparison with natural CURC, advantages related to the natural form of CURC include the facility to obtain the substance and greater possibility of using this therapeutic agent for clinical application in the future.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations